Pemanfaatan Teknologi Museum Virtual sebagai Sarana Pembelajaran Abad 21 - Kamila, Wafa; Kurniawan, Muhammad Rizky; Rahmawati, Nadia; Safitri, Sani; Oktapiani, Rani (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This article examines the use of virtual museum technology as a 21st century learning tool, with a focus on the integration of digital technologies such as virtual reality (VR) and augmented reality (AR) to increase student motivation, knowledge retention, and cognitive skill development. Through a descriptive qualitative approach based on literature reviews from indexed sources such as Scopus and Google Scholar (2015-2023), this research analyzes educational benefits, implementation challenges, and practical recommendations. Results show that virtual museums facilitate active, collaborative, and contextual learning, supporting 21st century competencies such as critical thinking, creativity, and digital literacy through immersive experiences that overcome geographic limitations. However, challenges such as the digital divide, content quality and teacher readiness need to be addressed. In the context of Indonesian education, this technology is in line with the Merdeka Curriculum and the Society 5.0 era, encouraging project-based innovation and strengthening ethical character. This research provides recommendations for educators and policy makers to optimize virtual museums as an inclusive and effective digital learning transformation tool.